Evaluation of the efficiency of Lidocaine 2%with Epinefrine 1:100000 buffered by sodium bicarbonates on intraoral regional anesthesia (Journal of Hama University, 2021)
In this retrospective study, 2% lidocaine with 1:100000 epinephrine buffered with 8.4% sodium carbonate efficiency was studied, we studied the anesthesia onset time, injection pain, and the duration of anesthesia, the sample consisted of 15 male patients  aged from 19 to 45 years injected with the anterior infra-orbital injection and IANB injection with and without buffering with sodium carbonate.Anesthesia onset time in sodium carbonate buffered anterior infra-orbital injection was decreased by 0.07 minutes compared with the conventional injection, and that was not statistically significant. And in the buffered IANB injection the onset of anesthesia decreased 0.87 minutes compared with the conventional injection, and that was statistically significant difference (p=0.048).Anesthesia duration was also decreased by 8 minutes in the buffered infra-orbital injection compared with the conventional injection, and this was statistically significant difference (p=0.21) and in the buffered IANB injection the duration was also decreased by 19.6 minutes, and that was statistically significant difference. (P = 0.010)The pain induced by the buffered infra-orbital injection was decreased statistically significant by 2 degrees (P = 0.001), and was decreased in the buffered IANB injection by 1 degree (P = 0.007).We concluded that buffering the anesthetic ampule with sodium bicarbonate may induce lesser pain during injection and may decrease the onset time, but may affect negatively on the anesthesia duration